BOSISME DALAM PROSES ELEKTORAL (Studi Tentang Strategi Bosisme Dalam Mempengaruhi Proses Elektoral di Kabupaten Halmahera Barat) - , Andre Demitrius,SIP; , Drs. Ratnawati, S.U. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The dynamics of legislative elections in West Halmahera District underwent many changes in line with decentralization as part of the political system in managing the country. These changes, at least give two senses, first, with a decentralized system the society will be increasingly active in determining any government policy and directly involved in any political process. Second, these changes also bring local bossism that has the capital to participate in any political process and manipulate public interest. This study shows that bossism practice which was run by Namto occurred in West Halmahera district by performing a variety of political intimidation to achieve political purposes, in conducting political activities in the election starting from the recruitment of members of the Regional Election Commission (Komisi Pemilihan Umum Daerah) until the determination of the election of members of the West Halmahera District Parliament. As happened in legislative election in 2009 that the PDI-P that should get four seats got seven seats when set up. Several diagnostic factors that affect so that Namto did so are because they have capital, have power to influence policy of the election organizers as well as have networks throughout both formal and non formal institutions to recruit their people in elections. In 2009 legislative election, Namto with the Indonesian Democratic Party of Struggle (PDIP) became the winner by gaining seven seats. Besides, the PDIP and Namto also put some people who should not sit as a member of parliament but, when they were set by the Regional Election Commission (KPUD) they sit as members of Regional Parliament (DPRD). As Prosperous Indonesian Party, in the first determination Steven Taliawo was set to sit but in the second determination it turned into Foni Suwatalbessi, National Democratic Party in the first determination did not sit as a member of parliament but in the second determination it did. Likewise National Concerned-People Party in the first determination was set as a regional parliament member but in the second determination it was not a member anymore. The same thing happened to Prosperous Peace Party which in the first determination Dominggus Eny was set as a regional parliament member, but in the second determination the name was replaced by Kerri Wangean. As well PDI-P in the first determination it was Agil Bopeng but in the second determination it was replaced by Orpoh Dihonggo. Namto did so because it has social, economic, and politic capitals that can be used in conducting political activities. In 2009 legislative election Namto was the key actor which was known as bossism with strategies: first, doing intervene in the recruitment of members of the Regional Election Commission, second, a strong network and controlling the election organizer. All these were done by Namto to secure all political policies by putting its people in government formal institutions.